An assessment of the potential impact of the introduction of male mammographers into the National Health Service breast screening programme. Issue 4 (November 2020) - Haddock, G.; Harcombe, J.; Jenkins, J.; Mackie, A.; Witney, C.
Abstract: Introduction: The NHS breast screening programme only employs female mammographers to carry out breast screening. The screening service is experiencing a shortage of staff and introducing male mammographers into the service is a potential solution. This research aimed to determine if the introduction of male mammographers would impact acceptance rates of the offer of screening, how women feel about the potential change and what the impact would be at a programme level. Methods: The research was conducted in 3 stages. Initially 24 face-to-face interviews were conducted with women aged 45–70 and 19 interviews over the telephone with stakeholders; these interviews explored what women's reaction would be to the introduction of male mammographers. These interviews informed the content of a questionnaire that was completed online by 1000 women aged 50–71. It explored what women would do if offered a test with a male mammographer and how they felt about the potential change. Results: Over half, 53.4% stated they would attend a routine mammogram if the mammographer was male, 15.3% said they would attend if a female chaperone was present, and 31.3% stated they would refuse to attend. The face-to-face interviews suggested women view routine breast screening differently to other healthcare interactions because it is an optional service and not a treatment. As a result, participants had higher expectations both in terms of expecting a choice over the gender of the mammographer and a need to feel comfortable. Conclusion and implications for practice: The findings indicate that the percentage of eligible women attending breast screening may decrease if male mammographers were introduced. This impact of introducing male mammographers would need to be carefully weighed up against the potential gains in workforce numbers in opening up mammography to male practitioners.